Mechanical properties of tender coconut (Cocos nucifera L.): Implications for the design of processing machineries. (26th December 2019) - Pandiselvam, R.; Manikantan, M. R.; Balasubramanian, D.; Beegum, P. P. Shameena; Mathew, A. C.; Ramesh, S. V.; Hebbar, K. B.; Niral, V.
Abstract: The mechanical properties such as punching force, cutting force, punching energy, and cutting energy of tender coconut at its different orientations are pertinent for the design and development of efficient and ergonomic tender coconut processing machineries viz., punch and cutter, trimming machine, and snowball machine. However, the mechanical properties of tender coconut have not been investigated scientifically yet. Hence, the mechanical properties of tender coconut at six different positions were determined. Four genotypes of tender coconut were used in this study, such as Andaman Giant Tall (AGT), Chowghat Orange Dwarf (COD), Kulasekaran Green Dwarf (KGD), and Ganga Bondam Green Dwarf (GBGD). A laboratory‐scale texture analyzer with a customized probe for cutting and punching was developed and used for the measurements. The highest punching and cutting force was observed at the bottom section (near fruit base) of the tender coconuts followed by the middle and top section. The maximum punching energy (2.23 J) in fruit top loading position was recorded for GBGD, whereas the minimum punching energy (0.82 J) was observed for the genotype AGT. The highest cutting energy of 11.79, 15.53, and 16.59 J recorded for AGT at flat loading position (top, middle, and bottom, respectively). Statistical analysis indicates that genotypes and loading positions of tender coconut significantly ( p  ≤ .01) affected the punching and cutting force. Practical applications: The basic information of tender coconuts including physical and mechanical properties is crucial for the design and development of tender coconut processing machinery. Earlier, we have reported the physical properties of tender coconuts necessary for the development of a trimming machine. As a follow‐up, herein we present the mechanical properties of tender coconut that are essential for the design of components such as punching and cutting tool, knife settings in trimming machine and the rotor design in snowball machine. This is the first scientific report highlighting the mechanical properties of the tender coconuts.